Distribución y taxonomía de Pyrgophorus platyrachis (Caenogastropoda: Hydrobiidae), en el Sistema de Maracaibo, Venezuela - Nava, Mario (Universidad de Costa Rica, 2011)
The presence of a microgastropod identified as Potamopyrgus sp. was detected previously in the Maracaibo System; nevertheless, a detailed morphological analysis identified this snail in other genera. The objective of this work is to update the distribution and taxonomy of Pyrgophorus platyrachis in the Maracaibo System, Venezuela in samples obtained between 2001 and 2009. The presence of hundreds of individuals of P. platyrachis were observed in the estuary, indeed in the localities of the Gran Eneal lagoon (4 111 snails), Peonías lagoon (229 snails), Punta Capitán Chico (758 snails), San Francisco (2 517 snails), Curarire (240 snails), Apon River mouth (173 snails), Ojeda City (240 snails), Bachaquero (128 snails) and Tomoporo de Agua (385 snails). We performed a taxonomical analysis, and emphasized in ecological aspects, such as the distribution of the species and habitat features, as near vegetation and type of associated sediment. We found three morphotypes of the species, one smooth, another with spiral striations and the other with spines. Smooth morphotype was exclusive of the Gran Eneal lagoon, Peonías lagoon, Punta Capitan Chico and Apon River mouth localities, whereas the other two morphotypes were found together in the remaining localities. According to our detailed anatomical and taxonomical analysis we propose a synonymy between P. platyrachis and the other species described like Pyrgophorus parvulus and Pyrgophorus spinosus.